1992
DOI: 10.1128/iai.60.8.3244-3252.1992
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of capsulate Haemophilus influenzae with human airway mucosa in vitro

Abstract: Two pairs of isogenic capsulate and noncapsulate and one pair of capsulate fimbriate and nonfimbriate strains of Haemophilus influenzae type b were studied in an organ culture of human respiratory mucosa. Over 24 h, the numbers of recovered bacteria increased from the original inoculum size of 10i to 108 CFU/ml. Transmission electron microscopy and scanning electron microscopy showed that noncapsulate organisms caused significant epithelial damage, whereas capsulate strains did not. Association of noncapsulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…Studies with adenoids and nasal turbinate tissue in organ culture indicate that piliated organisms tend to adhere to areas of damaged epithelium [101–103]. To underscore the potential role of pili in H. influenzae colonization, Weber et al demonstrated that, in yearling monkeys, the density of colonization was greater for piliated H. influenzae type b than for isogenic non‐piliated organisms with an insertionally inactivated hifA gene [104].…”
Section: Establishment On the Mucosal Surfacementioning
confidence: 99%
“…Studies with adenoids and nasal turbinate tissue in organ culture indicate that piliated organisms tend to adhere to areas of damaged epithelium [101–103]. To underscore the potential role of pili in H. influenzae colonization, Weber et al demonstrated that, in yearling monkeys, the density of colonization was greater for piliated H. influenzae type b than for isogenic non‐piliated organisms with an insertionally inactivated hifA gene [104].…”
Section: Establishment On the Mucosal Surfacementioning
confidence: 99%
“…Haemophilus influenzae infections, including otitis media, sinusitis, pneumonia, and persistent infections in chronic bronchitis patients, are preceded by airway colonization, which is a process facilitated by fimbria (8,24,32,39,54). Four families of fimbriae have been distinguished morphologically (5).…”
mentioning
confidence: 99%
“…This protein is supposed to have role in the modulation of fimbria expression genes, PUR and ILE, and inhibit their translation. The airway colonization of H. influenzae in host is facilitated by fimbria (Read et al 1992;Van Alphen and van Ham 1994). This hypothetical protein may even serve as mammalian tumor-associated antigen.…”
Section: Discussionmentioning
confidence: 99%